Enhancing Multistage Deep-Drawing and Ironing Manufacturing Processes of Axisymmetric Components: Analysis and Experimentation. (29th May 2014) - Ramírez, F. Javier; Domingo, Rosario; Packianather, Michael S.; Sebastian, Miguel A.
Abstract : An optimization technique for combined processes of deep-drawing and ironing has been created in order to improve the total process time and cost in manufacturing procedures of axisymmetric components. The initial solution is optimized by means of an algorithm that minimizes the total time of the global process, based on relationship between lengths, diameters, and velocities of each stage of a multistage process and subject to constraints related to the drawing ratio. The enhanced solution offers a significant reduction in time and cost of the global process. The final results, applied to three cases, are compared with experimental results, showing the accuracy of the complete solution.